2012
DOI: 10.1017/s1751731111002709
|View full text |Cite
|
Sign up to set email alerts
|

Impact of chicory inclusion in a cereal-based diet on digestibility, organ size and faecal microbiota in growing pigs

Abstract: A total of 30 7-week-old pigs were used to evaluate the effects of chicory inclusion on digestibility, digestive organ size and faecal microbiota. Five diets were formulated: a cereal-based control diet and four diets with inclusion of 80 and 160 g/kg chicory forage (CF80 and CF160), 80 g/kg chicory root (CR80) and a mix of 80 g/kg forage and 80 g/kg chicory root (CFR). Generally, the pigs showed a high growth rate and feed intake, and no differences between the different diets were observed. The coefficients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 35 publications
1
29
1
Order By: Relevance
“…The T-RFLP analysis showed that CFO increased species related to Prevotellacea in feces, and the results were confirmed with the qPCR analysis. The results are in contrast with previous studies where CFO was included in diets to growing pigs (Ivarsson et al, 2012a;Liu et al, 2012). In those studies, species related to Prevotella decreased in abundance with inclusion of CFO.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The T-RFLP analysis showed that CFO increased species related to Prevotellacea in feces, and the results were confirmed with the qPCR analysis. The results are in contrast with previous studies where CFO was included in diets to growing pigs (Ivarsson et al, 2012a;Liu et al, 2012). In those studies, species related to Prevotella decreased in abundance with inclusion of CFO.…”
Section: Discussioncontrasting
confidence: 99%
“…The TRF profile for each pig was based on two T-RFLP profiles; only peaks that occurred in both replicates were used for analysis. Subsequently, TRFs of interests were identified using sequence data of corresponding TRFs obtained from previous studies (Ivarsson et al, 2012a;Liu et al, 2012).…”
Section: Experimental Design and Dietsmentioning
confidence: 99%
“…Chicory pectin, a specific dietary component, appears to contribute to HSP expression in the porcine gut. Coupled with our previous findings on interactions between dietary chicory fiber and gut microbiota community composition in young pigs (24,29), we have gained a better understanding of the host-microbe interactions that shape the immune system. Further elucidation of the complex networking involved may allow precise manipulations of gut health to be achieved by dietary intervention.…”
Section: Discussionmentioning
confidence: 83%
“…In previous studies, we showed that inclusion of chicory forage and root in a cereal-based diet alters the pig gut microenvironment due to variations in chemical composition of the dietary fiber, highlighting the importance of chicory pectin, inulin-type fructan, and cereal arabinoxylan content (24,29). Therefore daily ingestion of different fiber fractions by pigs was evaluated in the present study (Table 3).…”
Section: Microbiota Complexity Varies In Different Regions Of Porcinementioning
confidence: 93%
See 1 more Smart Citation